WHAT ARE THE PATTERNS OF DYING IN ACUTE STROKE?. Issue Volume 5: Issue (2015)Supplement 1 (1st March 2015) - Burton, C; Turner, M; Payne, S
Abstract : Introduction: Implementation of stroke professionals' palliative care role outlined in the UK National Clinical Guidelines for stroke is challenged by uncertainty about prognosis. Understanding the patterns of dying in acute stroke may help stroke clinicians improve implementation. Aim(s) and method(s): To identify the patterns of dying in acute stroke services, and explore patient and family carer experiences. Over a six month period, biographical and clinical data, including the type of dying trajectory for deceased patients, were collected from admissions to four acute stroke services. Death trajectories were classified as sudden; rapid; episodic; slow decline; or other. Interviews were conducted with a sample of patients, family carers and bereaved relatives, exploring narratives of experience and initiation of end of life care. Results: 686 admissions were screened; with 627 (91.4%) eligible for inclusion. Six patients, nine family members and two bereaved family members took part in interviews. There were 91 deaths during the study period (14.5% of stroke patients) with dying trajectories classified for 72 deceased patients. Five (7.3%) were classed as sudden deaths; 64 (88.6) as rapid; 2 (3.3%) as episodic and 1 (0.8%) as slow decline. Interviews highlighted the significance that patients and families attach to clinical geography, including the type of care setting, in making sense of prognosis, and helpful messages that staff could use around planning for end of life care. Conclusion(s): The pattern of dying that acute stroke service staff encounter most is a rapid decline in a patient's condition, with a distinct terminal phase, although not set within a context of deterioration.